2006
DOI: 10.1021/bi052052c
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Indication for Myristoylation-Dependent Conformational Changes in HIV-1 Nef

Abstract: The accessory HIV-1 Nef protein is essential for viral replication, high virus load, and progression to AIDS. These functions are mediated by the alteration of signaling and trafficking pathways and require the membrane association of Nef by its N-terminal myristoylation. However, a large portion of Nef is also found in the cytosol, in line with the observation that myristoylation is only a weak lipidation anchor for membrane attachment. We performed biochemical studies to analyze the implications of myristoyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 49 publications
(61 reference statements)
8
68
2
1
Order By: Relevance
“…The interaction depends on a well conserved surface-exposed hydrophobic patch, reported to form an interface between Nef molecules in crystals of the Nef core domain (45). However, myristylated Nef is predominantly monomeric in solution (46,47), and the binding site for Dyn2 would thus be expected to be accessible on native Nef. Mutations that inhibited Dyn2 binding also impaired the infectivity enhancement function of Nef, as did the siRNA-mediated depletion of Dyn2.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction depends on a well conserved surface-exposed hydrophobic patch, reported to form an interface between Nef molecules in crystals of the Nef core domain (45). However, myristylated Nef is predominantly monomeric in solution (46,47), and the binding site for Dyn2 would thus be expected to be accessible on native Nef. Mutations that inhibited Dyn2 binding also impaired the infectivity enhancement function of Nef, as did the siRNA-mediated depletion of Dyn2.…”
Section: Discussionmentioning
confidence: 99%
“…However, the factors leading to lauroylation remain unclear, and the degree of lauroylation seems to be highly variable and inconsistent. Indeed, other studies based on this myristoylation strategy (both in rich and in minimal media) did not report the formation of a lauroylated form 15, 17, 18…”
Section: Introductionmentioning
confidence: 95%
“…After membrane targeting, Nef is rapidly internalized though interaction of its C-terminal flexible loop and cell proteins involved in the endocytic pathways. It has been shown that while Nef is in its membrane-bound form it appears more compactly folded, suggesting that membrane-bound and cytossolic Nef shown distinct accessible interaction domains (Breuer et al, 2006), which could explain the distinct phenotypes of Nef. Nef's ability to dimerize or even oligomerize can also function as a mechanism of regulating Nef's effects (Breuer et al, 2006;Dennis et al, 2005).…”
Section: Cellular Activation By Nefmentioning
confidence: 99%
“…It has been shown that while Nef is in its membrane-bound form it appears more compactly folded, suggesting that membrane-bound and cytossolic Nef shown distinct accessible interaction domains (Breuer et al, 2006), which could explain the distinct phenotypes of Nef. Nef's ability to dimerize or even oligomerize can also function as a mechanism of regulating Nef's effects (Breuer et al, 2006;Dennis et al, 2005). Exogenous Nef have been shown to enter monocytes/macrophages, B cells and Dendritic Cells (DC) by adsorptive endocytosis.…”
Section: Cellular Activation By Nefmentioning
confidence: 99%